2022
DOI: 10.34172/jrhs.2022.84
|View full text |Cite
|
Sign up to set email alerts
|

Time to Kidneys Failure Modeling in the Patients at Adama Hospital Medical College: Application of Copula Model

Abstract: Background: Kidney failure is a common public health problem around the world. The vast majority of kidney failure cases in Sub-Saharan African nations, including Ethiopia, go undetected and untreated, resulting in practically certain mortality cases. This study was aimed primarily to model the time to (right and left) kidneys failure in the patients at Adama Hospital Medical College using the copula model. Study design: A retrospective cohort study. Methods: The copula model was used to examine join time to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This solidifies the idea that the time to bi-variate events are related. [25][26][27][28] The study also shows that there was a clustering (frailty) effect, which may have been influenced by the heterogeneity in the patients' countries of origin, given that those from the same region share similar risk factors for cervical cancer. 29,30 The study found that age significantly increased both the death and relapse rates for women with cervical cancer.…”
Section: Discussionmentioning
confidence: 77%
“…This solidifies the idea that the time to bi-variate events are related. [25][26][27][28] The study also shows that there was a clustering (frailty) effect, which may have been influenced by the heterogeneity in the patients' countries of origin, given that those from the same region share similar risk factors for cervical cancer. 29,30 The study found that age significantly increased both the death and relapse rates for women with cervical cancer.…”
Section: Discussionmentioning
confidence: 77%
“…A vast array of applications is possible in survival/reliability analyses since the definition of "event" is arbitrary, not restricted to death. The events can be the appearance of tumor lesions and the onset/recurrence of diseases [5], progression of tumor [9], kidney failure [22], migraine [23], cognitive impairment [24], and others. The event could also be a good event, such as remission [5], return to work [25], marital pregnancy [26], and others.…”
Section: Definition Of Survival Timementioning
confidence: 99%
“…It can fit the joint distribution of a variety of different distribution variables. At present, it is widely used in nonlinear relationships in finance, wind power, water conservancy, and other fields, but is still poorly used in the medical field ( 11 13 ). Espasandín-Domínguez et al.…”
Section: Introductionmentioning
confidence: 99%